Modified straw as well as preparation method and application thereof

Through potassium permanganate modified rice straw, the problem of low remediation efficiency of cadmium-contaminated soil in the existing technology is solved, efficient cadmium adsorption and soil improvement are achieved, and economic and social effects of cadmium-contaminated soil restoration are provided.

CN119114024APending Publication Date: 2024-12-13HUNAN AGRI UNIV

Patent Information

Application Number
CN202411535466.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has low repair efficiency in cadmium-contaminated soil repair, and the adsorption performance of modified biochar to cadmium is poor, so it cannot be effectively used for water or soil repair.

Method used

Using potassium permanganate to modify rice straw, the hydroxyl and carboxyl groups of cellulose and hemicellulose are converted into potassium carboxylate through shock reaction, loading MnO2, improving the adsorption capacity of cadmium, forming modified straws for cadmium removal in water bodies and soil repair.

Benefits of technology

A high cadmium adsorption capacity is achieved, with a theoretical adsorption capacity of 257.6 mg/g. It can be effectively used for cadmium removal and cadmium-contaminated soil repair in water bodies, while increasing the K content in the soil and improving soil fertility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114024A_ABST
    Figure CN119114024A_ABST
Patent Text Reader

Abstract

The invention discloses modified straw and a preparation method and application thereof.The modified straw is obtained by modifying straw through a potassium permanganate solution, the concentration of the potassium permanganate solution is 60 g / L-120 g / L, and the mass ratio of the straw to potassium permanganate is 1: 2.4-4.8. The modified straw disclosed by the invention is simple in preparation method and high in cadmium adsorption capacity, can be used for adsorbing cadmium in a water body and repairing cadmium-polluted soil, and also can be used for improving the soil fertility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cadmium pollution treatment, and more specifically, relates to a modified straw and a preparation method and application thereof. Background Art

[0002] Cadmium pollution not only has a negative impact on the degradation of organic matter in the soil, soil ammoniation and nitrification, but also converts into more polluting metal-organic compounds, causing greater harm to human health and soil. The main methods for treating soil cadmium pollution include immobilization / stabilization, leaching, soil washing, electrochemical remediation, chemical reduction, phytoremediation and microbial remediation, but the overall remediation efficiency is low.

[0003] my country is rich in agricultural straw resources and is the world's largest straw country, with total output ranking first. Straw can generally be divided into the following ways of utilization: straw energy application, straw return to the field, straw feed application, straw industrial utilization, straw edible fungus base material, abandonment and incineration. Among them, most of the straw is discarded or burned, which not only causes serious waste of resources, but also may cause environmental pollution problems. In recent years, straw is usually made into biochar for the treatment and restoration of polluted water or soil. Chinese patent CN 104722267A discloses a modified biochar, which uses agricultural waste corn straw and rice straw, and is calcined into biochar after potassium permanganate modification as an adsorption material for heavy metal cadmium in polluted water bodies. However, the adsorption capacity of the adsorbent material is only 9.48 mg / g, and the adsorption performance of cadmium is poor, and it cannot be used in the remediation of cadmium-contaminated soil.

[0004] Therefore, developing adsorption materials for remediation of cadmium-contaminated water or soil using straw as raw material has high economic value and social effect. Summary of the invention

[0005] The purpose of the present invention is to provide a modified straw and a preparation method and application thereof, using straw as a raw material and potassium permanganate as a modifier, so that the modified straw has a higher cadmium adsorption capacity and can be used in cadmium removal from water or restoration of cadmium-contaminated soil.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A modified straw is obtained by modifying straw with a potassium permanganate solution, wherein the concentration of the potassium permanganate solution is 60g / L-120g / L, and the mass ratio of the straw to the potassium permanganate is 1:2.4-4.8.

[0008] Furthermore, the straw is rice straw.

[0009] Furthermore, the straw is crushed and then passed through a 40-mesh sieve.

[0010] Furthermore, the pH of the potassium permanganate solution is 1-13.

[0011] Furthermore, the pH of the potassium permanganate solution is 6-8.

[0012] The preparation method of the modified straw is as follows: 1g of straw is washed and dried, crushed and sieved through a 40-mesh sieve for later use; added to a potassium permanganate solution with a concentration of 60g / L-120g / L and shaken for reaction for 20-24h, then washed, filtered, dried, and ground through a 100-mesh sieve.

[0013] The modified straw is used for cadmium adsorption in water or passivation of cadmium-contaminated soil.

[0014] In the present invention, the structure of rice straw is changed mainly by converting the hydroxyl and carboxyl groups of cellulose and hemicellulose into potassium carboxylate, and MnO2 is loaded on the material, and cadmium is adsorbed mainly by exchanging potassium ions in potassium carboxylate with cadmium ions in water or soil. In the present invention, there is no need to carbonize the straw, so as to obtain a better cadmium adsorption capacity.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention designs a simple modification method for straw, and the modified straw with cadmium adsorption capacity can be obtained only by soaking in potassium permanganate, and the preparation method is simple. The modified straw has a strong adsorption capacity for cadmium, and the theoretical adsorption capacity is 257.6 mg / g. It can be applicable to the removal of cadmium in water bodies and the restoration of cadmium-contaminated soil. When used for the restoration of cadmium-contaminated soil, it can also increase the K content in the soil and improve the soil fertility, providing a way for the high-value transformation of straw. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 To improve the adsorption performance of straw on cadmium in water;

[0018] (a) Cadmium removal performance of straw modified with KMnO4 at different concentrations; (b) Cadmium removal performance of straw material modified with 70 g / L KMnO4 under acidic, neutral and alkaline conditions (experimental conditions: pH = 5.0, Cd(II)0 = 200 mg / L, dosage 1 g / L, adsorption 6 h).

[0019] Figure 2 The changes of ion concentrations of acMRS (a), neMRS (b) and alMRS (c) during the adsorption process (experimental conditions: pH = 5.0, Cd (II) 0 = 200 mg / L, dosage 1 g / L, adsorption 6 h)

[0020] Figure 3(a) Kinetic fitting and (b) isothermal adsorption fitting analysis of neMRS.

[0021] Figure 4 These are the SEM spectra of RS (a, e), acMRS (b, f), neMRS (c, g) and alMRS (d, h), and (i), (j), (k) and (l) are the EDS spectra.

[0022] Figure 5 Characterization profiles of RS, acMRS, neMRS, and alMRS;

[0023] Among them, (a) XRD pattern, (b) FT-IR pattern and (c) XPS full spectrum, XPS fine spectrum of C1s (d), Mn2p (e), O1s (f)

[0024] Figure 6 N2 adsorption-desorption isotherms of RS (a), acMRS (b), neMRS (c) and alMRS (d).

[0025] Figure 7 This is a correlation analysis between the Mn content in the modified material and its adsorption performance.

[0026] Figure 8 :(a) Morphological analysis of Cd at different pH values, (b) Cd removal performance of neMR at different pH values, (c) Zero-point charge.

[0027] Fig. 9 The cadmium removal performance of neMRS in water;

[0028] Among them, (a) different material dosages, (b) different solution initial concentrations, and (c) different times.

[0029] Fig.10 The effect of coexisting anions and cations on the adsorption of Cd(II) by neMRS.

[0030] Fig.11 The change of soil pH after adding neMRS material;

[0031] Among them, (a) naturally contaminated soil, (b) simulated contaminated soil.

[0032] Fig.12 The changes of available Cd content in soil at 0, 7, 15, 30, and 60 days after adding neMRS materials;

[0033] Among them, (a) naturally contaminated soil, (b) simulated contaminated soil.

[0034] Fig.13The changes of available K content in soil at 0, 7, 15, 30, and 60 days after adding neMRS materials;

[0035] Among them, (a) naturally contaminated soil, (b) simulated contaminated soil.

[0036] Fig.14 The changes of different forms of Cd in soil after 15 and 60 days

[0037] Fig.15 These are longitudinal comparison photos of pea growth. DETAILED DESCRIPTION

[0038] To make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be described in further detail below in conjunction with embodiment, but the embodiments of the present invention are not limited thereto. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by the technicians belonging to the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. It should be noted that, unless otherwise specified, the reagents used in the present embodiment, etc. are all common commercial products.

[0039] Example 1

[0040] Modification with different potassium permanganate concentrations: First, wash the rice straw with deionized water and dry it, then crush it and pass it through a 40-mesh sieve for later use. Weigh 0, 0.4, 0.8, 1.6, 2.0, 2.4, 2.8, 3.2 and 4.8 g of KMnO4 in a 100 mL conical flask, add 40 mL of deionized water to dissolve, then add 1 g of treated rice straw powder to the conical flask, and place it in a constant temperature shock box at 25 ° C for 24 hours. Then wash, filter and dry, grind and pass through a 100-mesh sieve for later use. The straw materials modified with different KMnO4 concentrations were named RS, 10MRS, 20MRS, 40MRS, 50MRS, 60MRS, 70MRS, 80MRS and 120MRS.

[0041] Example 2

[0042] Potassium permanganate modification with different pH values: Weigh 2.8 g of KMnO4 in a 100 mL conical flask, dissolve it with 0.1 mol / L HCl, H2O and NaOH, and obtain KMnO4 solutions with pH values ​​of 1, 7 and 13, respectively. Then add 1 g of treated rice straw powder to the conical flask, and place it in a constant temperature shaker at 25 ° C for 24 hours. Then wash, filter and dry, grind through a 100 mesh sieve for later use. The straw materials modified with KMnO4 with different pH values ​​were named acMRS (acidic), neMRS (neutral) and alMRS (alkaline).

[0043] Experimental conditions: 50 mL of 200 mg / L Cd(II) solution was added to a 100 mL conical flask, the pH of the solution was adjusted to 5 using 0.1 mol / L NaOH and HCl, acMRS, neMRS and alMRS were added at a dosage of 1.0 g / L, and adsorbed in an oscillator at 25 °C for 6 h. Three parallel groups were set for each experiment. After standing for 30 min, the solution was filtered with a 0.45 μm filter membrane and the concentrations of Cd, K and Mn in the solution were measured using inductively coupled plasma atomic emission spectrometry.

[0044] like Figure 1 As shown in (a), the adsorption capacity of modified straw materials for Cd is greater than that of the original straw material RS. The KMnO4 concentration has a great influence on the adsorption capacity of modified straw for Cd. When the KMnO4 concentration is less than 70g / L, the adsorption capacity of modified straw for Cd increases with the increase of KMnO4 concentration; when the KMnO4 concentration is greater than 70g / L, the adsorption capacity of modified straw for Cd is stable at about 172mg / g and no longer changes with the change of KMnO4 concentration. Figure 1 As shown in (b), the acid-base environment of KMnO4 also affects the ability of modified straw to adsorb Cd. The neMRS obtained in neutral KMnO4 has the best adsorption capacity for Cd, reaching 171.8 mg / g; followed by the alMRS obtained in alkaline KMnO4, with an adsorption capacity of 150.4 mg / g; the worst is the acMRS obtained in acidic KMnO4, with an adsorption capacity of 119.1 mg / g.

[0045] Figure 2 The dynamic concentration changes of Mn, Cd and K ions during the adsorption process of acMRS, neMRS and alMRS are shown. After 6 hours of adsorption by acMRS, neMRS and alMRS, the Mn ion concentrations in the solution were stabilized at 5.6, 0.20 and 1.2 mg / L, respectively, while the changes in the Cd and K ion concentrations in the solution showed opposite trends. After 6 hours, the Cd ion concentrations in the solution were 89.9, 31.0 and 34.2 mg / L, respectively, and the K ion concentrations were 123.3, 202.4 and 181.4 mg / L, respectively. This indicates that the K ions in the adsorbent skeleton exchanged with the Cd ions and released into the aqueous solution, participating in the adsorption process of Cd. The removal capacity of acMRS, neMRS and alMRS for Cd is affected by the release of K ions. During the modification process, due to the release of H in the acidic environment, + and K + The competition between NaOH and CO makes it more difficult to generate COO-K and CO-K in acMRS. + With K +In alMRS, COO-Na and CO-Na compete to form. Under neutral conditions, there is no H + and Na + interference, so K + Can be loaded onto neMRS more easily.

[0046] The pseudo-first-order and pseudo-second-order kinetic models were used to fit the cadmium removal behavior of neMRS, such as Figure 3 As shown in (a), the adsorption kinetics of neMRS conforms to the pseudo-second-order kinetic model (R 2 =0.9937, Table 1), indicating that the adsorption process is mainly chemical adsorption. The adsorption isotherm is of great significance for studying the interaction between the adsorbent and the adsorbed pollutant. Figure 3 As shown in (b), the Langmuir and Freundlich models were used to fit the cadmium removal behavior of neMRS. The adsorption isotherm of neMRS was consistent with the Langmuir isotherm adsorption model (R 2 =0.9979, Table 2), the adsorption process belongs to single molecule adsorption, and the theoretical maximum adsorption capacity for Cd(II) is 257.6 mg / g.

[0047] Table 1 Fitting parameters of pseudo-first-order and pseudo-second-order adsorption kinetic models of neMRS for Cd

[0048]

[0049] Table 2 Fitting parameters of Langmuir and Freundlich isotherm adsorption models of neMRS for Cd

[0050]

[0051] Performance Testing

[0052] 1. Characterization

[0053] The surface morphology and crystal structure of the adsorbent were characterized by X-ray diffractometer (XRD, Aeris, PANalytical, Holland) and scanning electron microscopy (SEM-EDS, Sigma 300, ZEISS, Germany). The elemental composition and chemical valence of the adsorbent were analyzed by X-ray photoelectron spectroscopy (XPS, K-Alpha, THERMO Scientific, America). The surface functional groups of the adsorbent were analyzed by Fourier transform infrared spectrometer (FT-IR, Alpha, Bruker, Germany). The specific surface area and pore size dispersion were determined by Brunauer-Emmett-Teller method (BET, JW-BK100, JWGB, China).

[0054] The characterization analysis of RS, acMRS, neMRS and alMRS by SEM, XRD, FTIR and XPS proved that KMnO4 modification would make the cellulose structure of straw disappear and load MnO2 on the surface of the material. By analyzing the mechanism of KMnO4 modification of rice, it was concluded that KMnO4 mainly changes the structure of rice straw by converting the hydroxyl and carboxyl groups of cellulose and hemicellulose into potassium carboxylate. Figure 4 The surface morphology and structure of RS, acMRS, neMRS and alMRS are shown. Figure 4 (a) and Figure 4 (e)) is relatively smooth, while acMRS ( Figure 4 (b) and Figure 4 (f))、neMRS( Figure 4 (c) and (g)) and alMRS( Figure 4 The surfaces of (d) and (h) are relatively rough and contain a large number of loose particles, indicating that KMnO4 has damaged the surface structure of rice straw. Figure 4 (i)- Figure 4 As shown in (l), it can be observed from the EDS image of neMRS that C, O, K and Mn elements are distributed on the surface of neMRS, indicating that after KMnO4 modification, K and Mn elements are successfully loaded on the surface of the material.

[0055] The crystal structure of rice straw before and after KMnO4 modification was tested, and the XRD patterns are shown in Figure 5(a). The XRD diffraction pattern of RS has three peaks at 15.0°, 22.6° and 40.5°, which match the crystal planes (110), (021) and (004) of cellulose. After modification with KMnO4, the XRD diffraction patterns of acMRS, neMRS and alMRS show characteristic peaks at 36.9° and 66.0°, which match the crystal planes (311) and (440) of MnO2 (JCPDS No.42-1169). And the characteristic peaks of cellulose in the sample disappear, indicating that KMnO4 as a reactant destroys the crystal structure of cellulose in RS and loads MnO2 on the modified straw material.

[0056] Fourier infrared analysis of modified straw materials at 500-4000cm -1 Functional group changes within the frequency range, the results are as follows Figure 5 (b) is shown. Located at 3427, 3374, 3418 and 3404 cm -1 The absorption peaks at 2919 cm-1 represent the hydroxyl groups (-OH) on the surface of RS, acMRS, neMRS and alMRS. -1The peak intensity at 1728 cm in RS is significantly weakened compared with that at 1728 cm in RS, indicating that the polycyclic sugars in cellulose and hemicellulose in the modified straw material are reduced, which is consistent with the above XRD results. -1 The absorption peak at 1728 cm-1 in acMRS, neMRS and alMRS is caused by the stretching vibration of the carbonyl (C=O) on the side chain of the lignin structural unit. -1 The absorption peaks at 1637, 1544 and 1411 cm -1 The enhanced signals of the absorption peaks of 1052cm-1 were attributed to the carboxyl group (COO-), indicating that KMnO4 increased the number of carboxyl groups on the surface of the modified straw. -1 The absorption peak at 525cm represents the Si-O in silicon dioxide (SiO2). The weakening of this band indicates that SiO2 has been partially broken after modification. Among the four samples, the peak intensity of Si-O in neMRS is the weakest, which indicates that neutral KMnO4 has a stronger ability to destroy the SiO2 structure. -1 A new absorption peak characteristic of Mn-O appeared at the surface, verifying the formation of MnO2 on the surface of the modified straw.

[0057] The surface composition and valence of RS, acMRS, neMRS and alMRS were analyzed by XPS technology. Figure 5 As shown in (c), due to the modification of KMnO4, Mn and K elements appear on the surface of acMRS, neMRS and alMRS. The C1s spectrum of RS is shown in Figure 5 As shown in (d), there are three peaks at 284.5, 286.5 and 288.8 eV, representing CC, CO and C=O, respectively. After modification with KMnO4, the C=O ratios in acMRS, neMRS and alMRS increased from 5.1% to 27.4%, 13.0% and 16.6%, respectively. This is because the strong oxidant (KMnO4) reacts with RS, resulting in the oxidation and cleavage of the macromolecular chains in RS. In addition, the Mn2p spectrum is shown in Figure 5 (e) Mn2p at 654.9 eV and 643.4 eV were found in acMRS, neMRS, and alMRS, respectively. 1 / 2 and Mn2p 3 / 2 The peak spacing is 11.5 eV, proving that MnO2 exists on the surface of the straw material after being modified by KMnO4. The O1s spectrum of RS is shown in Figure 5 As shown in (f), there are two peaks at 532.9eV and 531.9eV, representing CO and C=O, respectively. After modification, a new peak representing metal oxide (MO) appeared at 529.8eV. Combined with the results of Mn2p, it is shown that there is abundant MnO2 on the surface of acMRS, neMRS and alMRS.

[0058] Table 3 Specific surface area and pore volume of RS, acMRS, neMRS and alMRS

[0059]

[0060]

[0061] The specific surface area and pore size distribution of RS, acMRS, neMRS and alMRS are shown in Figure 6 As shown in Table 3. The specific surface area of ​​neMRS (18.44m 2 / g) is much higher than RS (0.48m 2 / g)、acMRS(11.09m 2 / g) and alMRS (4.40m 2 / g), indicating that the pore expansion effect of neutral KMnO4 on RS is better than that of other conditions. The isotherm of neMRS conforms to the type III H3 type of the IUPAC standard, indicating that it has a mesoporous structure and an irregular pore structure. In addition, the average pore size of neMRS (12.8nm) is smaller than that of RS (57.6nm), acMRS (27.1nm) and alMRS (44.5nm), further confirming that KMnO4 regulates the pore structure of RS.

[0062] Table 4 Mn content in modified straw materials

[0063]

[0064] In order to further explore the mechanism of KMnO4-modified rice straw, all the prepared modified materials were acid-hydrolyzed and the Mn content was tested. The results are shown in Table 4. When the KMnO4 concentration was less than 70 g / L, the Mn content in the modified straw increased with the increase of KMnO4 concentration; when the KMnO4 concentration was greater than 70 g / L, the Mn content in the modified straw was stable at about 411 mg / g and no longer changed with the change of KMnO4 concentration. The Mn content of neMRS obtained in neutral KMnO4 is greater than that of alMRS and acMRS. The correlation analysis between the Mn content in the material and its adsorption capacity for Cd is as follows: Figure 7 As shown, we get R 2 ≈0.984, indicating that the adsorption capacity of modified straw is closely related to the Mn content in it.

[0065] The contents of cellulose, hemicellulose and lignin in RS, acMRS, neMRS and alMRS were determined by the NREL method. The mass percentages of cellulose, hemicellulose and lignin in RS, acMRS, neMRS and alMRS (Table 5) were 29.3% / 16.8% / 28.3%, 0 / 0 / 15.9%, 0 / 0 / 25.5% and 0 / 0 / 23.9%, respectively. Since cellulose and hemicellulose have more hydroxyl groups, after modification with KMnO4, the hydroxyl groups are easily oxidized to carboxyl groups. + It can also replace the H on the carboxyl and hydroxyl groups + , resulting in the disappearance of cellulose and hemicellulose components in acMRS, neMRS and alMRS. Lignin, as a polyphenolic substance, is composed of three phenylpropanol monomers (p-coumaryl alcohol, coniferyl alcohol and sinapyl alcohol), which is difficult to be oxidized by KMnO4. Therefore, the lignin content of acMRS, neMRS and alMRS only decreased by 12.4%, 2.8% and 4.4%, respectively.

[0066] Table 5 Mass percentage of lignin, cellulose and hemicellulose in RS, acMRS, neMRS and alMRS

[0067]

[0068] 2. neMRS as an adsorbent to remove Cd(II) from water

[0069] In order to further analyze the key factors affecting Cd removal by neMRS, three variables, namely, initial pH of the solution, material dosage, and initial concentration of Cd(II) solution, were investigated.

[0070] (1) Investigate the effect of initial solution pH on adsorption effect

[0071] Add 50 mL of 200 mg / L Cd(II) solution to a 100 mL conical flask, adjust the solution pH to 2-7 with 0.1 mol / L NaOH and HCl, add neMRS at a dosage of 1.0 g / L, and adsorb for 6 h in an oscillator at 25 °C. Each experiment was set up in parallel with 3 groups. After standing for 30 min, filter with a 0.45 μm filter membrane and measure the residual concentration in the solution using inductively coupled plasma atomic emission spectrometry.

[0072] Visual MINTEQ 3.1 software was used to calculate the speciation distribution of Cd in aqueous solutions at different pH values. Figure 8 As shown in (a), when pH < 8, it mainly exists in the form of Cd(II). Figure 8(b) shows the effect of initial pH of 2-7 on the Cd adsorption performance of neMRS. When pH = 3-6, the Cd removal rate of neMRS is stable at about 88%; when pH = 2, the Cd removal rate drops to 9.7%. It is speculated that the protonation of the adsorbent surface makes H + At low pH levels, Cd 2+ Easier to adsorb on the adsorbent surface. Figure 8 (c) shows that the zero-point charge of neMRS is 8.84. When the pH is lower than pHpzc, the adsorbent is positively charged. When the pH is higher than pHpzc, the adsorbent is negatively charged due to the release of protons from the surface. Therefore, the surface of neMRS is positively charged, which is not conducive to electrostatic adsorption because Cd(II) also has a positive charge.

[0073] (2) Investigate the effect of material dosage on adsorption effect

[0074] 50 mL of 200 mg / L Cd(II) solution was added to a 100 mL conical flask, the pH of the solution was adjusted to 5 using 0.1 mol / L NaOH and HCl, and neMRS was added at dosages of 0.2, 0.6, 1.0, 1.4, and 2.0 g / L, respectively, and adsorbed in an oscillator at 25 °C for 6 h. Three parallel groups were set for each experiment. After standing for 30 min, the residual concentration in the solution was measured using inductively coupled plasma atomic emission spectrometry after filtering with a 0.45 μm filter membrane.

[0075] like Fig. 9 As shown in (a), under the premise that the initial solution concentration, pH value, adsorption time and solution volume remain unchanged, the removal rate of Cd by neMRS increases with the increase of adsorbent dosage. The adsorption amount of Cd by the adsorbent shows an inflection point at a dosage of 1.0 g / L, first increasing and then decreasing. Because when the dosage is less than 1.0 g / L, the surface active sites of the adsorbent are relatively small and can reach a saturated state during the adsorption process, so the adsorption amount of cadmium increases with the increase of dosage, and the adsorption amount can reach 168.5 mg / L. When the adsorbent dosage is more than 1.0 g / L, as the dosage increases, the cadmium ions in the solution are not enough to fill the active sites of the adsorbent, which manifests as complete adsorption of cadmium. However, the adsorption amount of cadmium per unit mass decreases, so the adsorption capacity of the three adsorbents for cadmium decreases.

[0076] (3) Investigate the effect of initial solution concentration on adsorption effect

[0077] 50 mL of 50, 100, 200, 300, 400 and 500 mg / L Cd(II) solution was added to a 100 mL conical flask, the pH of the solution was adjusted to 5 using 0.1 mol / L NaOH and HCl, neMRS was added at a dosage of 1.0 g / L, and adsorbed in an oscillator at 25 °C for 6 h. Three parallel groups were set for each experiment. After standing for 30 min, the residual concentration in the solution was measured using inductively coupled plasma atomic emission spectrometry after filtering with a 0.45 μm filter membrane.

[0078] like Fig. 9 As shown in (b), with the increase of initial concentration, the adsorption capacity of neMRS for Cd continues to increase, while the removal rate of Cd continues to decrease. This is because at lower concentrations, there are enough adsorption sites on the surface of neMRS, showing a higher removal rate. With the increase of initial concentration, the adsorption sites gradually become saturated, while the total number of adsorption sites on the adsorbent remains unchanged, which increases the adsorption capacity of neMRS per unit mass for Cd and finally maintains at around 229.0 mg / g. (4) Investigate the effect of different time on adsorption effect

[0079] Add 50 mL of 200 mg / L Cd(II) solution to a 100 mL conical flask, adjust the solution pH to 5 with 0.1 mol / L NaOH and HCl, add neMRS at a dosage of 1. g / L, and adsorb for 6 h in an oscillator at 25 °C. Sampling is performed at 20, 30, 60, 120, 240, and 480 min, respectively. Three parallel groups are set for each experiment. After standing for 30 min, the residual concentration in the solution is measured by inductively coupled plasma atomic emission spectrometry after filtering with a 0.45 μm filter membrane.

[0080] like Fig. 9 As shown in (c), the adsorption of Cd by neMRS also consists of a rapid stage (0-20 min) and a slow stage (20-1440 min). This process is the same as that of cellulose adsorbent. In the rapid stage, the adsorption rate is relatively fast in the first 20 minutes, the adsorption capacity increases rapidly with time, and the adsorption sites are gradually filled. The removal rate of Cd by neMRS reaches 69.9%. Subsequently, the adsorption process enters a slow stage, the adsorption sites reach saturation, and the adsorption amount tends to stabilize. After 5 hours, the equilibrium state is reached, the removal rate of Cd is 86.5%, and the maximum adsorption capacity is 173.1 mg / g.

[0081] (5) Anion and cation interference experiment

[0082] Before adding neMRS, 0.1 mol / L sodium sulfate (Na2SO4), sodium chloride (NaCl), sodium nitrate (NaNO3), potassium chloride (KCl), magnesium chloride (MgCl2) and calcium chloride (CaCl2) were added to the solution as competitive ions and added to 50 mL of aqueous solution containing Cd. The conical flask was placed in a constant temperature oscillator at 25°C for 6 hours and then the Cd concentration in the solution was measured.

[0083] Depend on Fig.10 It can be seen that the seven ions will affect the removal of cadmium by neMRS to varying degrees. 2- 4. Cl - 、NO3 - and Na + When K + , Ca 2+ and Mg 2+ When the two coexist, the efficiency of neMRS in removing cadmium is greatly reduced, which is reduced to 68.53%, 50.50% and 31.92% respectively. + , K in solution + Will inhibit the K of neMRS + is released into the solution. 2+ and Mg 2+ Both carry two positive charges, and Cd 2+ Due to their similar structures, there is a competitive relationship during the adsorption process, which reduces the removal of cadmium by neMRS.

[0084] 3. Removal of Cd(II) from soil by neMRS

[0085] (1) Artificial simulation of cadmium-contaminated soil

[0086] The soil used in this experiment was taken from Changsha County, Changsha City, Hunan Province (itself cadmium-contaminated soil, total cadmium content of 1.26 mg / kg). The soil was naturally dried and ground through a 10-mesh sieve to screen out stones and other impurities in the soil. A certain amount of Cd(II) stock solution was added to the soil, stirred and mixed, and then aged at room temperature for 15 days. After natural air drying and grinding through a 10-mesh sieve, a cadmium-contaminated soil with a concentration of 2.57 mg / kg was obtained.

[0087] (2) Test method

[0088] Soil pH determination: According to the agricultural industry standard of the People's Republic of China (NY / T1377-2007), weigh 10 g of air-dried, ground and 10-mesh sieve soil sample, place it in a 25 mL centrifuge tube, add 25 mL of ultrapure water to maintain a soil-water ratio of 1:2.5, stir for 5 minutes, let it stand for 1 hour, and then measure the pH with a pH meter.

[0089] Determination of available cadmium: CaCl2 method was used for testing. Weigh 5.00 g of air-dried, ground and 10-mesh sieved soil sample and 25 mL of 0.1 mol / L CaCl2 solution, shake for 2 h, filter and test.

[0090] Quick-acting potassium test: Use CH3COONH4 extraction method. Weigh 5.00g of air-dried, ground and 10-mesh sieve soil sample and 50mL 0.1mol / L CH3COONH4 solution, shake for 0.5h, filter and test.

[0091] Determination of cadmium forms: The BCR continuous extraction method was selected to divide the cadmium in the soil into four forms: weak acid extractable state (Wa), oxidized state (Ox), reducible state (Res) and residual state (Red).

[0092] (3) Experiment on removal of Cd(II) from soil by neMRS

[0093] Four treatments and two blank controls were set up with material dosage and soil concentration as variables. First, 200g of natural cadmium-contaminated soil (cadmium content of 1.26mg / kg) and artificial simulated cadmium-contaminated soil (cadmium content of 2.57mg / kg) were weighed in plastic boxes, and neMRS was added to the soil at a dosage of 0.5% and 2.0%, respectively, and stirred evenly. Three parallels were set for each treatment. A certain amount of ultrapure water was added to the plastic box regularly to ensure that the soil moisture content was maintained between 60-70%; the box was placed in a constant temperature box (25°C) and samples were taken at 0, 7, 14, 30, and 60d, air-dried, ground, and sieved for testing. The pH value changes, effective cadmium content, available potassium content, and morphological cadmium content of the soil samples to be tested were measured.

[0094] Table 6 pH value changes of soil samples tested

[0095]

[0096] Table 6 and Fig.11The figure shows the change of soil pH after adding neMRS for 60 days. The pH of both natural contaminated soil and simulated contaminated soil increased significantly after adding neMRS and remained relatively stable for 60 days. The addition of 0.5% increased the pH of natural contaminated soil by about 2.5 and the pH of simulated contaminated soil by about 1.0; the addition of 2.0% increased the pH of natural contaminated soil by about 3.7 and the pH of simulated contaminated soil by about 1.8. The experimental soil itself is acidic and contains more H + After adding neMRS, the H + Will be with K on neMRS + Ion exchange is carried out to increase the pH in the soil. The more neMRS is added, the more obvious the change in soil pH is.

[0097] Table 7 Available Cd content of soil samples to be tested

[0098]

[0099] Table 7 and Fig.12 The figure shows the change in the available Cd content in the soil 60 days after the addition of neMRS. Seven days after the addition of neMRS, the available Cd content in the soil dropped significantly and remained relatively stable within 60 days. The addition of 0.5% reduced the available Cd content in the natural contaminated soil from 0.384 mg / kg to 0.101 mg / kg, and the soil solidification rate reached 73.7%; the available Cd content in the simulated contaminated soil decreased from 1.910 mg / kg to 1.273 mg / kg, and the soil solidification rate was 33.3%; the addition of 2.0% had a solidification rate of 93.8% in the natural contaminated soil and 67.5% in the simulated contaminated soil. The solidification rate of available Cd in the natural contaminated soil is large, and the pH changes are large; the solidification rate of available Cd in the simulated soil is small, and the pH changes are small. This shows that the K above neMRS + Will give priority to Cd 2+ The naturally contaminated soil contains lower Cd content, and the K + with cd 2+ After the exchange, there are more K + Can be combined with H in the soil + exchange, so the pH change in the naturally contaminated soil is large. However, due to the high Cd content in the simulated contaminated soil, a large amount of K + with cd 2+ Exchange, only a small amount of K + With H + exchange, resulting in smaller pH changes in simulated contaminated soils.

[0100] Table 8 Changes of available potassium in soil

[0101]

[0102] Table 8 and Fig.13 The figure shows the change in soil available K content 60 days after the addition of neMRS. After the addition of neMRS, the available K in the soil showed a trend of first rising and then slowly falling. The addition of 0.5% increased the available K content in natural contaminated soil from 15.267 mg / kg to 455.20 mg / kg, and the available K content in simulated contaminated soil from 64.940 mg / kg to 578.77 mg / kg; the addition of 2.0% increased the available K concentration in natural contaminated soil and simulated contaminated soil to about 1500 mg / kg. This confirms the above K + with cd 2+ Exchange description, neMRS will greatly increase the content of available K in the soil and improve soil fertility.

[0103] In order to further analyze the morphological changes of Cd in soil, the BCR method was used to analyze the Cd forms in soil. Cd exists in soil mainly in four chemical forms: residual state (Res), oxidizable state (Ox), reducible state (Red) and weak acid extractable state (Wa), which directly affect its bioavailability and environmental behavior. Fig.14 As shown in the figure, the contents of four forms of Cd in different samples fluctuated at different times, but Wa-Cd and Red-Cd were the main forms. Wa represents Cd that can be exchanged by ions or in carbonates and is more easily bioavailable, and Red represents Cd bound in the form of iron and manganese oxides in the soil. After 15 days of treatment with 0.5% and 2.0% neMRS, the percentages of Wa-Cd and Red-Cd in the soil changed significantly. 0.5% neMRS reduced the Wa-Cd content from 57.3% to 50.8% and increased the Red-Cd content from 34.0% to 39.9%; 2.0% neMRS reduced the Wa-Cd content from 57.3% to 53.8% and increased the Red-Cd content from 34.0% to 36.4%. This indicates that neMRS can convert Cd that is easily absorbed by plants into Cd that is more difficult to be absorbed and utilized by plants. The percentage changes of Wa-Cd and Red-Cd contents after 60 days of treatment with 0.5% and 2.0% neMRS also showed similar results, indicating that neMRS significantly reduced the potential toxicity and bioavailability of Cd in soil.

[0104] (4) Plant growth experiment

[0105] First, pea seeds were germinated in a constant temperature incubator, and then the seeds were transferred to untreated natural contaminated soil and natural contaminated soil with 0.5% neMRS added. After the pea seeds were cultured in the incubator for 15 days, the pea sprouts were pulled out, and the growth of the pea seedlings and the development of the root system were observed and compared. The pea seedlings and roots were separated, washed with deionized water and dried at 60°C for 24 hours. There were 4 parallel samples in each potted plant, and the Cd content in the pea sprouts was analyzed by inductively coupled plasma mass spectrometry.

[0106] In the control group, Cd was mainly accumulated in the roots of pea, with a concentration of 10.34 mg / kg. The Cd content in the stems and leaves was 1.40 mg / kg. The addition of neMRS reduced the Cd content in the roots to 3.91 mg / kg, a decrease of 62.2%, and the Cd content in the stems and leaves to 0.38 mg / kg, a decrease of 72.8%. + It is beneficial for pea germination. Fig.15 As shown, K in soil + The release of neMRS also made the pea sprouts grow vigorously. At 15 days, the root system of the potted pea seedlings added to the soil was more developed than that of CK, and the plants were more luxuriant. Therefore, the plant growth experiment proved the feasibility of neMRS in reducing cadmium and fertilizing soil.

[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A modified straw, characterized in that: The modified straw is obtained by modifying the straw with a potassium permanganate solution, the concentration of the potassium permanganate solution is 60g / L-120g / L, wherein the mass ratio of the straw to the potassium permanganate is 1:2.4-4.

8.

2. The modified straw according to claim 1, characterized in that: The straw is rice straw.

3. The modified straw according to claim 1, characterized in that: The straw is crushed and passed through a 40-mesh sieve.

4. The modified straw according to claim 1, characterized in that: The pH of the potassium permanganate solution is 1-13.

5. The modified straw according to claim 1, characterized in that: The pH of the potassium permanganate solution is 6-8.

6. The method for preparing the modified straw according to any one of claims 1 to 5, characterized in that: Wash and dry 1g of straw, crush it and pass it through a 40-mesh sieve for later use; add it to a potassium permanganate solution with a concentration of 60g / L-120g / L and shake it for 20-24h, then wash, filter and dry it, and grind it through a 100-mesh sieve.

7. Use of the modified straw according to any one of claims 1 to 5 in removing cadmium from water or passivating cadmium-contaminated soil.

Citation Information

Patent Citations

  • Preparation method of absorbing material for heavy metals of polluted water body

    CN104722267A

Cited By

  • Modified straw material, preparation method thereof and thallium treatment method

    CN121060477A